"Gotta Go Now": Rethinking the Use of the Mighty and Simon Birch - Katrina Arndt; Julia M. White; Andrea Chervenak (Disability Studies Quarterly, 2009)
Critical film analysis in the context of disability studies is introduced, and implications of disability portrayals in film are discussed. Two films often used in middle school classrooms, Simon Birch and The Mighty, are introduced and briefly summarized. The films are critiqued using Norden’s conceptualizations of stereotypic roles for characters with disabilities including the "sweet innocent" and "comic misadventurer." Finally, the importance of critical screening is outlined and ways that teachers can use these films in ways that are respectful of people with disabilities based on criteria developed by Safran (2000) are offered.